Analysing the critical quality factors in IoT-based serviceimplementation: A systematic evaluation - Sidek N.; Ali N.B. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The emergence of InternetofThings offers opportunities for public services to deliver efficient and high-quality smart services. At present, the IoT-based services (IoTbS)are still at an initial stage of the journey to Governments digital transformation. Although the success of IoTbSimplementation depends on users' behaviour and their willingness to use, little attention has been paid to explore the critical quality factors (CQFs) of IoTbSthat may influence the usage and performance. This article presents the currentstate of IoTbSimplementation and will answer these questions: 1) What are the CQFsthat influence the usage and performance of IoTbSimplementation?; and2) What are the research types and research contribution types in this area? In this study, a systematic literature reviewwas performed using specific search string to obtain papers recently published from four relevant electronic databases. As a result, the systematic search yielded 10,066 hits and 11 papers were selected presenting CQFs in this context. Besides identifying the CQFs, research types and contribution types in IoTbSimplementation, this paper reports the identified research gaps that have led the author to recommend potential future directions on this topic. BEIESP.